2022
DOI: 10.1002/anie.202116068
|View full text |Cite
|
Sign up to set email alerts
|

Clusters Induced Electron Redistribution to Tune Oxygen Reduction Activity of Transition Metal Single‐Atom for Metal–Air Batteries

Abstract: Oxygen reduction reaction (ORR) activity can be effectively tuned by modulating the electron configuration and optimizing the chemical bonds. Herein, a general strategy to optimize the activity of metal single‐atoms is achieved by the decoration of metal clusters via a coating–pyrolysis–etching route. In this unique structure, the metal clusters are able to induce electron redistribution and modulate M−N species bond lengths. As a result, M‐ACSA@NC exhibits superior ORR activity compared with the nanoparticle‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
145
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 277 publications
(148 citation statements)
references
References 55 publications
3
145
0
Order By: Relevance
“…Downsizing active species to a single-atom scale not only promotes the maximum atom utilization efficiency but also results in unique electronic properties for tuning binding strength with reaction intermediates. Generally, the geometric and electronic structures of atomic metal sites can be engineered by their local coordination environment with other elements (O, B, S, P, etc. ). , However, it is difficult to modify the electronic structures merely through the introduction of heteroatoms due to the reason of the poor control of uniformity and dispersion. , Notably, controlling the long-range activation through interfacial interaction created by electron-donating/-withdrawing species can be a promising approach for tuning the electronic structure of single metal centers. Sub-nanometric metal clusters exhibited excellent catalytic performance because of coordinatively unsaturated surface atoms, resulting in electron delocalization and tunable electronic properties. , …”
Section: Introductionmentioning
confidence: 99%
“…Downsizing active species to a single-atom scale not only promotes the maximum atom utilization efficiency but also results in unique electronic properties for tuning binding strength with reaction intermediates. Generally, the geometric and electronic structures of atomic metal sites can be engineered by their local coordination environment with other elements (O, B, S, P, etc. ). , However, it is difficult to modify the electronic structures merely through the introduction of heteroatoms due to the reason of the poor control of uniformity and dispersion. , Notably, controlling the long-range activation through interfacial interaction created by electron-donating/-withdrawing species can be a promising approach for tuning the electronic structure of single metal centers. Sub-nanometric metal clusters exhibited excellent catalytic performance because of coordinatively unsaturated surface atoms, resulting in electron delocalization and tunable electronic properties. , …”
Section: Introductionmentioning
confidence: 99%
“…28 enhanced ORR activity. 29 As a result, it is feasible to enhance the catalytic activity of the SA-Fe−N−C catalyst with numerous N−Fe−N 4 moieties near atomic Fe clusters. Moreover, in most of the previous studies of SA-Fe−N−C that utilized ZIF as the precursors, it has been revealed that the catalysts will inherit the microporous structures of the precursors.…”
Section: Introductionmentioning
confidence: 99%
“…Also, the adsorption of oxygen-containing intermediates on the central Fe atoms with σ-type bonding would be greatly modulated during the ORR process. Thus, the generated *OH intermediates on the central metal atom can pull the central Fe back into the N 4 plane and convert the spin state of Fe centers from high back to low, eventually reducing the energy barrier for the ORR process. ,, In addition, it is reported that the electronic structure of single-atom sites can be also modified by the existence of the atomic clusters nearing these single-atom sites . For example, Huang et al reported that a Fe cluster-decorated SA-Fe–N–C catalyst with a unique electronic configuration, which shows that the redistribution of electrons on Fe–N 4 centers induced by atomic clusters exhibits an enhanced ORR activity . As a result, it is feasible to enhance the catalytic activity of the SA-Fe–N–C catalyst with numerous N–Fe–N 4 moieties near atomic Fe clusters.…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide energy crisis prompted extensive and methodical study into energy conversion and storage. [1][2][3][4] Electrocatalytic oxygen reduction reactions (ORR), [5,6] hydrogen evolution reactions (HER) [7] and oxygen evolution reactions (OER) [8] play an important role in various energy technologies, including fuel cells [9][10][11][12] and water splitting. [13][14][15] The development of efficient electrocatalysts for energy conversion and storage is particularly critical.…”
Section: Introductionmentioning
confidence: 99%